Creating Sustainable Supply of Sugarcane through Contract Farming Partnership (A Case Study at Sugar Factory “Kebon Agung”, Malang – Indonesia) - Kartika DS Susilowati; Asminah Rachmi; Nur Indah Riwajanti (International Journal of Supply Chain Management, 2020)
Employing an interpretive research design with post-positivist paradigm, it was conducted in Kebon Agung Sugar Factory, Malang. The research informants were selected using snowballing technique. The informants include farmers and chairmen of farmers groups, plantation staff, company employees, and government agencies. To maintain the continuity and loyalty of sugarcane farmers to the company, the sugar factories provide various facilities, such as credit, inputs, guidance and counseling as well as technological assistance, and market guarantees for the products produced. The provision of incentives and facilities to partner sugarcane farmers is not merely for helping them meet their needs, but also for binding the farmers so that the sugarcane farmers are willing to sell all of their sugar to the Sugar Factory. To create supply sustainability of the sugar cane, the factory made several efforts including giving rewards to farmers with the best performance, providing sympathetic service and guidance, prioritizing loyal farmers and maintaining farmers’ trust